2009
DOI: 10.1167/9.12.12
|View full text |Cite
|
Sign up to set email alerts
|

The fate of task-irrelevant visual motion: Perceptual load versus feature-based attention

Abstract: We tested contrasting predictions derived from perceptual load theory and from recent feature-based selection accounts. Observers viewed moving, colored stimuli and performed low or high load tasks associated with one stimulus feature, either color or motion. The resultant motion aftereffect (MAE) was used to evaluate attentional allocation. We found that task-irrelevant visual features received less attention than co-localized task-relevant features of the same objects. Moreover, when color and motion feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 52 publications
2
45
1
Order By: Relevance
“…This strategy need not necessarily be conscious. The reason for thinking that this may be important is that key results on context obtained with the method of single stimuli (Taya et al 2009; Turi and Burr 2012) have not been confirmed using the two-alternative (2AFC) technique we describe here (Morgan 2013, 2014). The technique (technically ‘two-interval forced choice with a roving pedestal’) is to present two stimuli in temporal succession rather than one and to ask the subject to decide which of the two is nearer to the 6 o’clock position.…”
Section: Introductionmentioning
confidence: 83%
“…This strategy need not necessarily be conscious. The reason for thinking that this may be important is that key results on context obtained with the method of single stimuli (Taya et al 2009; Turi and Burr 2012) have not been confirmed using the two-alternative (2AFC) technique we describe here (Morgan 2013, 2014). The technique (technically ‘two-interval forced choice with a roving pedestal’) is to present two stimuli in temporal succession rather than one and to ask the subject to decide which of the two is nearer to the 6 o’clock position.…”
Section: Introductionmentioning
confidence: 83%
“…In the third group (see Fig. 1C), PL is increased by making it more difficult to discriminate among the possible targets (Bahrami, Carmel, Walsh, Rees, & Lavie, 2008;Brand-D'Abrescia & Lavie, 2007;Cartwright-Finch & Lavie, 2007;Couperus, 2001;Handy & Mangun, 2000;Taya, Adams, Graf, & Lavie, 2009). In the fourth group (see Fig.…”
Section: Perceptual Loadmentioning
confidence: 99%
“…A valid precue indicating the location of the target eliminates the PL effect (Chen & Cave, 2013Johnson, McGrath, & McNeil, 2002;Miller, 1991;Paquet & Craig, 1997), as does confining the relevant and irrelevant information to the same object or spatial region (Chen, 2003;Taya et al, 2009), or prolonging the duration of the target display until response (Roper, Cosman, Mordkoff, & Vecera, 2011;. A distractor or nontargets that are in the same hemisphere as the target will reduce distractor processing compared to a distractor or nontargets in different hemispheres (Torralbo & Beck, 2008;Wei, Kang, & Zhou, 2013).…”
Section: Perceptual Loadmentioning
confidence: 99%
“…However, psychophysical, imaging, and electrophysiological studies showed that attending towards a certain object feature is associated with enhanced processing of that feature throughout the visual field (Rossi and Paradiso, 1995; Treue and Martínez Trujillo, 1999; McAdams and Maunsell, 2000; Saenz et al, 2002; Arman et al, 2006; Müller et al, 2006; Serences and Boynton, 2007). In addition, various recent studies indicated that selection of a single target-object feature may result in suppression of other, task-irrelevant features of that object (Fanini et al, 2006; Nobre et al, 2006; Cant et al, 2008; Polk et al, 2008; Wegener et al, 2008; Serences et al, 2009; Taya et al, 2009; Xu, 2010; Freeman et al, 2014). …”
Section: Introductionmentioning
confidence: 99%